Efektivitas Pelayanan Dengan Keberhasilan Rekam Medis Elektronik Di Rumah Sakit Ibu Anak Athaya Medika - Situmorang, Masriani; Mulyana, Mulyana; Natasha, Natasha (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
Background: Athaya medika Hospital has organized Electronic Medical Records, but some health workers state that the success of Electronic Medical Records is not always in line with the improvement of service effectiveness in hospitals, Objective: To determine the relationship between the success of electronic medical records and service effectiveness and to determine the relationship between the success of electronic medical records and the quality of services at Athaya Medika Mother and Child Hospital Hospital. Method: The research method used is a quantitative descriptive method with a cross sectional approach.  This study was conducted from June to August, with a total of 60 respondents. Results: Based on the bivariate analysis test using Chi Square where the p-value is 0.042<0.05 and for the quality of service the p-value is 0.024<0.05 so it is said that there is a significant relationship between the success of Electronic Medical Records on the effectiveness of service and service quality. Conclusion: The Success of Electronic Medical Records at Athaya Medika Hospital is Included in the Good Category with a percentage with 60 respondents answering 80%.the effectiveness of the service category is very good with a percentage of 86.7% . The quality of service with the category is 71.7%. There was a significant relationship between success on service effectiveness with a p-value of 0.042 and a relationship between success and service quality with a p-value of 0,024.